The role of a personal assistant (personlig assistent) in the life of people with disabilities in Sweden - Agnieszka Rams (University of Applied Sciences in Tarnow, Poland, 2017)
In Sweden, people with disabilities can apply for personal assistance in the form of personlig assistent. The task of such personal assistant is to support the disabled person in the place of residence, in daily activities such as dressing, personal hygiene, and contact with other people. Assistants also serve as companions during walking, shopping and outings to the movies, trip on holiday or even at work. They enable the contact with the public, and above all, they give a sense of independence and integration. A personal assistant is a key to independent living of people with disabilities.